Environmental and Microbial Factors in Inflammatory Bowel Disease Model Establishment: A Review Partly through Mendelian Randomization - Zesheng Lin; Wenjing Luo; Kaijun Zhang; Shixue Dai (Gut and Liver, 2024)
Inflammatory bowel disease (IBD) is a complex condition resulting from environmental, microbial, immunologic, and genetic factors. With the advancement of Mendelian randomization research in IBD, we have gained new insights into the relationship between these factors and IBD. Many animal models of IBD have been developed using different methods, but few studies have attempted to model IBD by combining environmental factors and microbial factors. In this review, we examine how environmental factors and microbial factors affect the development and progression of IBD, and how they interact with each other and with the intestinal microbiota. We also summarize the current methods for creating animal models of IBD and compare their advantages and disadvantages. Based on the latest findings from Mendelian randomization studies on the role of environmental factors in IBD, we discuss which environmental and microbial factors could be used to construct a more realistic and reliable IBD experimental model. We propose that animal models of IBD should consider both environmental and microbial factors to better mimic human IBD pathogenesis and to reveal the underlying mechanisms of IBD at the immune and genetic levels. We highlight the importance of environmental and microbial factors in IBD pathogenesis and offer new perspectives and suggestions for improving experimental animal modeling. Our goal is to create a model that closely resembles the clinical picture of IBD.